1999
DOI: 10.1117/12.373409
|View full text |Cite
|
Sign up to set email alerts
|

<title>Gamut mapping in multiple color spaces</title>

Abstract: In the process of gamut mapping from monitor display into printer hardcopy in CIE L*a*b* color space, blue is tend to map to purple. This paper presents a new approach to solve the perceived blue hue shift problem. By this approach, the entire color gamut is divided into four regions: a non-blue region, a blue-region, and two in-between regions. The segmentation of the four regions is based on the hue angle in CIE L*a*b* color space. Different color spaces are applied to different regions for gamut mapping. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In our implementation, we set following default parameters, (w L , w h ) for the six primaries to determine aimed primaries: R (0.5, 0.5), G(0.75, 0.5), B(0.75, 0), C(0.75, 0.5), M(0.75, 0.75), Y (1,1). They are applied to generate sRGB color maps for the tradeoff between pictorials and business graphics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our implementation, we set following default parameters, (w L , w h ) for the six primaries to determine aimed primaries: R (0.5, 0.5), G(0.75, 0.5), B(0.75, 0), C(0.75, 0.5), M(0.75, 0.75), Y (1,1). They are applied to generate sRGB color maps for the tradeoff between pictorials and business graphics.…”
Section: Resultsmentioning
confidence: 99%
“…Without hue rotation, blue colors are mapped to purple during the gamut mapping from a monitor gamut to a printer gamut [1]. It was found that this problem came from the serious blue hue nonlinearity in CIELAB color space [2].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it must store a large amount of sample data, which limits computational efficiency. Zeng has developed a new GCR algorithm by directly converting CIEXYZ values to CMYK values. In this algorithm, the K amount can be flexibly controlled by users, but the precision is highly influenced by the additivity of colorimetric density.…”
Section: Introductionmentioning
confidence: 99%